Grip strength, muscle soreness and pain threshold perception evolution in baseball pitchers in a simulated 75-pitch game: a repeated measures study - Tremblay, M.; Sirois, S. A.; Abboud, J.; Descarreaux, M. (BMJ Open Sport & Exercise Medicine, 2025)
Background/aim In baseball pitching, neuromuscular fatigue and its manifestations on muscle strength, muscle soreness and pain perception affect pitching performance. The purpose of this study was to quantify the evolution of grip strength, muscle soreness and pain threshold perception and pitching velocity in baseball pitchers throughout a simulated 75-pitch game.